Asuhan Keperawatan Gerontik Pada Pasien Dengan Hipertensi Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Nathania Hasna Ariqah; Sandra Dewi; Kheniva Diah Anggita; Hasmita Hasmita (CV. ITTC INDONESIA, 2026)
According to the World Health Organization (WHO) in 2024, approximately 1 billion people worldwide suffer from hypertension, with a prevalence of 26.6% in men and 26.1% in women. In Indonesia, the prevalence of hypertension reaches 34% or about 63,309,620 people, while in West Sumatra it is recorded at 27.8%. Hypertension is a cardiovascular disorder characterized by an increase in blood pressure, with systolic blood pressure of ≥140 mmHg and/or diastolic blood pressure of ≥90 mmHg. This study aimed to provide gerontic nursing care for an elderly patient with hypertension. The research employed a case study method involving one client at Wisma Gunung Tigo, PSTW Sabai Nan Aluih Sicincin, Padang Pariaman Regency, from February 18 to 23, 2026. The nursing assessment identified three nursing diagnoses: ineffective health management, chronic pain, and risk of falls. The nursing interventions included health education, non-pharmacological pain management through deep breathing relaxation techniques, and identification of the client's safety needs. After five days of nursing implementation, the client demonstrated improved awareness of the disease, healthier lifestyle behaviors, reduced headache complaints, better blood pressure control, and a decreased risk of falls. It is expected that the client will routinely monitor blood pressure, adhere to medication therapy, and avoid factors that may worsen the condition. Caregivers are also expected to supervise and encourage regular health check-ups and treatment compliance.